Effects of dance intervention on frailty among older adults. (May 2020) - Meng, Xiangfei; Li, Guichen; Zhang, Guangwei; Yin, Huiru; Jia, Yong; Wang, Shuo; Shang, Binghan; Wang, Chunyan; Chen, Li
Highlights: Dance intervention may reduce the presence and severity of frailty in older adults. According to the frailty criteria, dance intervention reduced the prevalence of slowness, weakness, and low physical activity. Dance is a popular recreational activity and can be promoted as preventive strategies for frailty. Abstract: Objective: The aims of this study were to examine the effects of dance intervention on frailty in pre-frail and frail older persons. Design: This is a quasi-experimental, two-group trial. Setting: Older adults living nursing home. Participants: Participants aged ≥ 60 years with low physical activity (mean age was 81.8 years; 71 % were female) (N = 66). Methods: Participants allocated to the dance group attended 40 min dance sessions in a nursing home, three times a week for 12-weeks. Participants allocated to the control group maintained their normal daily activities. Assessments were conducted at baseline, 6 weeks, and 12 weeks by researchers blinded to the allocation. Frailty was measured based on Fried criteria. Estimates of frailty between groups over time were calculated using the generalized estimating equations (GEE) and mixed effects models. Results: The prevalence of frailty decreased over time in the dance group compared to the control group (P = 0.002). The mean frailty scores decreased 0.69 at 6 weeks and 1.06 at 12 weeks. Compared to the control group, the prevalence of slowness (p = 0.002), weakness (p = 0.005), and low physical activity (p < 0.001) significantly decreased in the dance group. Conclusions: Dance intervention may reduce the presence and severity of frailty in older adults. Slowness and low physical activity improve following 12 weeks of dance intervention.